Quantum State Tomography of Single Qubit Using Density Matrix - Bastian, Syafi’i Fahmi; Kalasuwan, Pruet; Purwanto, Joko (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The quantum state tomography is a fundamental part in the development of quantum technologies. It can be used to know the signal characterization of small particle called photon in the nanoscale. In this study, photon number has been measured in order to produce the states tomography. Optical devices and quantum-mechanical approaches were explored to obtain the quantum state tomography. Due to a single qubit state density matrix can be revealed by Stokes parameters, so there are four set-ups to measure the Stokes parameters for each sample. The density matrix is used because the pure state only appear theoreticaly. In the real experiment, It always exibits a mixed state. The samples of tomography measurements consist of linear state, cicular state and the IR 808nm. In this study, state tomography is shown by 2x2 density matrix. This experiment also provides the fidelities of experiment result. And it shows the good agreement. From this experiment, the state of IR 808nm has been detected. The laser that examined is showing a vertical state with fidelity F=97,34%.